OCULAR COMPLICATION AS A LONG-TERM SEQUELAE OF STEVEN-JOHNSON SYNDROME: WHAT SHOULD WE DO? - Monica Rizky Wigianita; Ismi Zuhria (Integrative Perspectives of Social and Science Journal, 2025)
Ocular surface abnormalities in SJS is a sequelae that has a high chance of progressing, especially in eyes with partial keratinization and conjunctivalization. Even after recovering from skin problems without sequelae, patients can have serious ocular complications leading to blindness despite local and systemic therapy. A 51 years old woman complained that both eyes were red and watery since three years. She also said that her both eyes felt stuck because the eyelashes turned inward for the past 3 years. Initially the patient suffered from SJS (Steven-Johnson Syndrome) in early 2020 with complaints of whole body blisters After the body condition gradually improved after SJS, the patient began to feel changes in the condition of both eyes. The visual acuity of the patient was 5/5 in both eyes. The Schirmer test were 15 mm in right eye and 5 mm in left eye. The Tear Break Up Time (TBUT) examination showed 3 second in right eye and 1 second in left eye. The eyelid had meibomian gland dysfunction for both eyes and the conjunctiva had symblepharon in both eyes. From fluorescein test showed multiple punctate in both eyes. The chronic ocular complications of SJS is characterized by a vicious cycle of ocular surface scarring and inflammation that disturbs the delicate structure and function of the eyelids and tear film and then progresses to further ocular surface damage and swelling. The long-term prognosis of the eye depends on early detection and intensive treatment. To identify the cicatrical abnormalities that cause chronic ocular surface failure, such as limbal cell deficiency and total ocular surface keratinization, the eyelid margin, palpebral conjunctiva, and fornix should be carefully examined.